Assessment of Anterior Segment Measurements With Optical Low-Coherence Refl ectometry and Scheimpfl ug Analysis Following Intravitreal Injection of Dexamethasone Implant - (:unkn) unknown (My University, 2017)
Amaç: İntravitreal deksametazon enjeksiyonu sonrası optik düşük koherens reflektometri ve Scheimpflug analizi ile alınan ön segment ölçümlerini karşılaştırmak.Gereç ve Yöntemler: Bu çalışmaya ven dal tıkanıklığı nedeniyle deksametazon implantı uygulanan 11 göz dahil edildi. Her iki cihaz ile intravitreal enjeksiyon öncesi ve sonrası, merkezi kornea kalınlığı, ön kamara derinliği, pupil çapı, keratometri (K) değerleri (dik ve düz meridyendeki K değerleri), korneal astigmatizma gücü ve silindir gücü ölçüldü. Parametreler arasındaki uyum Bland-Altman plot analizi ile değerlendirildi.Bulgular: Blant-Altman analizinde her iki cihazla elde edilen tüm verilerin (merkezi kornea kalınlığı, ön kamara derinliği, pupil çapı, dik K, düz K, korneal astigmatizma gücü ve silindir gücü) %95 uyum aralığı klinik olarak kabul edilebilir sınırlarda idi ve cihazlar arasında iyi bir uyum mevcuttu.Sonuç: Deksametazon implatının enjeksiyonu sonrası alınan bütün ön segment parametrelerinin değerlendirilmesi için her iki cihaz birbirinin yerine kullanılabilir.

Purpose: To compare the anterior segment measurements obtained with optical low-coherence reflectometry and Scheimpflug analysis following intravitreal injection of dexamethasone implant.Materials and Methods: This study enrolled eleven eyes with branch retinal vein occlusion implanted with dexamethasone implant. Central corneal thickness, anterior chamber depth, pupil diameter, keratometry (K) readings at the steepest meridian (steep K) and the flattest meridian (flat K), corneal astigmatism power, and cylinder axis were measured before and after intravitreal injection using the optical low-coherence reflectometry device and Scheimpflug analyzer. The degree of agreement between parameters was assessed using Bland-Altman plot analysis.Results: Central corneal thickness, anterior chamber depth, pupil diameter, steep K, flat K, corneal astigmatism power, and cylinder axis measurements with the optical low-coherence reflectometry device and Scheimpflug analyzer showed narrow 95% limits of agreement (LoA), which implies good agreement between two measurements. Conclusion: Both systems can be used interchangeably for all anterior segment measurements following intravitreal injection of dexamethasone implant.
İntravitreal Deksametazon Enjeksiyonu Sonrası Yapılan Optik Düşük Koherens Refl ektometri ve Scheimpfl ug Analizi ile Ön Segment Ölçümlerinin Objektif Değerlendirilmesi
Keywords: Göz Hastalıkları